Science, Media and Policy Collaboration in Practice: Bird Flu Case in Bali, Indonesia - Yohanes Widodo (Jurnal ILMU KOMUNIKASI, 2010)
Abstract : This paper discusses how science (scientist) and policy (government) collaborate on the bird flu case in Bali Indonesia and the importance of public participation in dealing with the case. It is concluded that the collaboration between science and policy in the bird flu case in Bali Indonesia has not well practiced. There is a gap and conflict between them because they have different analytical paradigm, interest, and point of view. Public participation is very important because it can encourage them to set up quick response mechanism and increase public awareness of the danger of the virus. So they can stop the spread of the virus by themselves